Adolescent friendships predict later resilient functioning across psychosocial domains in a healthy community cohort. Issue 13 (11th April 2017) - van Harmelen, A.-L.; Kievit, R. A.; Ioannidis, K.; Neufeld, S.; Jones, P. B.; Bullmore, E.; Dolan, R.; ,; Fonagy, P.; Goodyer, I.
Abstract : Background: Adolescence is a key time period for the emergence of psychosocial and mental health difficulties. To promote adolescent adaptive ('resilient') psychosocial functioning (PSF), appropriate conceptualisation and quantification of such functioning and its predictors is a crucial first step. Here, we quantify resilient functioning as the degree to which an individual functions better or worse than expected given their self-reported childhood family experiences, and relate this to adolescent family and friendship support. Method: We used Principal Component and regression analyses to investigate the relationship between childhood family experiences and PSF (psychiatric symptomatology, personality traits and mental wellbeing) in healthy adolescents (the Neuroscience in Psychiatry Network; N = 2389; ages 14–24). Residuals from the relation between childhood family experiences and PSF reflect resilient functioning; the degree to which an individual is functioning better, or worse, than expected given their childhood family experiences. Next, we relate family and friendship support with resilient functioning both cross-sectionally and 1 year later. Results: Friendship and family support were positive predictors of immediate resilient PSF, with friendship support being the strongest predictor. However, whereas friendship support was a significant positive predictor of later resilient functioning, family support had a negative relationship with later resilient PSF. Conclusions: We show that friendship support, but not family support, is an important positive predictor of both immediate and later resilient PSF in adolescence and early adulthood. Interventions that promote the skills needed to acquire and sustain adolescent friendships may be crucial in increasing adolescent resilient PSF.